A dynamic study of VEGF-A siDOX-EVs trafficking through the in-vitro insert co-culture blood-brain barrier model by digital holographic microscopy - Shamshiripour, Parisa; Rahnama, Mehrana; Nikoobakht, Mehdi; Hajiahmadi, Fahimeh; Moradi, Ali-reza; Ahmadvand, Davoud (Frontiers in Oncology, 2024)
Introduction Modeling the blood-brain barrier has long been a challenge for pharmacological studies. Up to the present, numerous attempts have been devoted to recapitulating the endothelial barrier in vitro to assess drug delivery vehicles’ efficiency for brain disorders. In the current work, we presented a new approach for analyzing the morphometric parameters of the cells of an insert co-culture blood-brain barrier model using rat brain astrocytes, rat brain microvascular endothelial cells, and rat brain pericytes. This analytical approach could aid in getting further information on drug trafficking through the blood-brain barrier and its impact on the brain indirectly. Methods In the current work, we cultured rat brain astrocytes, rat brain microvascular endothelial cells, and rat brain pericytes and then used an insert well to culture the cells in contact with each other to model the blood-brain barrier. Then, the morphometric parameters of the porous membrane of the insert well, as well as each cell type were imaged by digital holographic microscopy before and after cell seeding. At last, we performed folate conjugation on the surface of the EVs we have previously tested for glioma therapy in our previous work called VEGF-A siDOX-EVs and checked how the trafficking of EVs improves after folate conjugation as a clathrin-mediated delivery setup. the trafficking and passage of EVs were assessed by flow cytometry and morphometric analysis of the digital holographic microscopy holograms. Results Our results indicated that EVs successfully entered through the proposed endothelial barrier assessed by flow cytometry analysis and furthermore, folate conjugation significantly improved EV passage through the blood-brain barrier. Moreover, our results indicated that the VEGF-A siDOX-EVs insert cytotoxic impact on the cells of the bottom of the culture plate. Conclusion folate-conjugation on the surface of EVs improves their trafficking through the blood-brain barrier and by using digital holographic microscopy analysis, we could directly assess the morphometric changes of the blood-brain barrier cells for pharmacological purposes as an easy, label-free, and real-time analysis.